New and old wars - Kaldor, Mary. (Cambridge [England] ; Malden, MA : Polity Press, 2012)
Mary Kaldor's New and Old Wars has fundamentally changed the way both scholars and policy-makers understand contemporary war and conflict. In the context of globalization, this path-breaking book has shown that what we think of as war - that is to say, war between states in which the aim is to inflict maximum violence - is becoming an anachronism. In its place is a new type of organized violence or 'new wars', which could be described as a mixture of war, organized crime and massive violations of human rights. The actors are both global and local, public and private. The wars ar.
Introduction -- Old wars -- Bosnia-Herzegovina: a case study of a new war -- The politics of new wars -- The globalized war economy -- Towards a cosmopolitan approach -- The 'New War' in Iraq -- Governance, legitimacy and security.
"Organized violence in a global era"--Cover
Includes bibliographical references and index.
Print version record.
Keywords: Since 1989; Low-intensity conflicts (Military science); World politics -- 1989-; HISTORY -- Modern -- 20th Century; Low-intensity conflicts (Military science); Electronic books